PENGARUH INOVASI PRODUK DAN KESADARAN MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK GABINO (STUDI KASUS PADA KONSUMEN GABINO) - Desi Novita; Bambang Irawan (JAMBIS : Jurnal Administrasi Bisnis, 2022)
This study aims to determine the Effect of Product Innovation and Brand Awareness on Gabino Product Purchase Decisions (Case Study on Gabino Consumers). The research method used is a quantitative method. Data collection techniques used in the form of questionnaires and literature. The population of this research is consumers who use Gabino products at Metropolitan Mall Bekasi. The sampling technique in this research is non-probability sampling with population sampling method. The sample is 130 samples. Analysis of the data used is multiple linear regression analysis using IBM Statistics software version 25. The results of the study indicate that Product Innovation has an influence on Purchase Decisions by 42.2%. Brand Awareness has a 38.3% effect on Purchase Decision. Product Innovation and Brand Awareness have a significant effect on Purchase Decisions. Product Innovation and Brand Awareness affect the Purchasing Decision variable simultaneously with a value of 0.805 or 80.5% where 19.5% is explained by other factors not included in this study.